Representasi Kritik Sosial Dalam Naskah Drama “Wabah”, “Korupsi”, Dan “Baliho” Karya Tiga Dramawan Teater Koma: Perspektif Semiotika Ferdinand De Saussure - Juneta, Jessica; Hartati, Dian; Meliasanti, Ferina (Peneliti.net, 2024)
This study explored an analysis of the representation of socio-criticism using Saussure's semiotics perspective. Subjects of this study are drama scripts of “Plague” written by Budi Ros, “Corruption” written by Norbertus Riantiarno, and “Billboard” written by Rangga Riantiarno. Meanwhile, the object of this study is the representation of socio-criticism in drama scripts. The study intended to figure out the representation of socio-criticism in the three drama scripts. This study uses a qualitative approach and applies a descriptive analysis method. Data collection techniques used literature study and note-taking. The researcher looked for the three drama scripts, and then note-taking the required data. The researcher collected data from the three subjects to be composed based on predetermined categories and then analyzed the data. The analysis is written descriptively and systematically. The results of the study demonstrate that there are twenty-sixth dialogues representing socio-criticism in the three drama scripts which are dominated by Semar’s dialogue.